Equilibrium distance from long-range dune interactions - J. Vérité; C. Narteau; O. Rozier; J. Alkalla; L. Barrier; S. Courrech du Pont (Earth Surface Dynamics)
Flow perturbations induced by dune topography affect sediment transport locally but can also be felt over long distances, altering the dynamics of isolated neighbouring dunes downstream. In order to work under optimal conditions that eliminate transverse flow components, collisions, and mass exchange between dunes, we study here these long-range interactions using a 2D numerical model where two equal-sized dunes lying on a non-erodible bed are exposed to a symmetric reversing flow. Depending on the initial spacing, dunes either attract or repel each other to eventually converge towards a steady-state spacing. This equilibrium distance decreases with flow strength and increases with the period of flow reorientation and dune size. It is mainly controlled by the reversing dune shape and the structure of the turbulent wake it generates, which continuously modulates the mean shear stress on the downstream dune. Under multi-directional wind regimes, these long-range flow perturbations offer an alternative mechanism for wavelength selection in linear dune fields with non-erodible interdune areas. Within these dune fields, estimates of mean shear stress could be used to assess the relative migration rate and the state of attraction or repulsion between neighbouring dunes.